2005
DOI: 10.1097/00001610-200511000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Gastrostomy Tubes

Abstract: The first successful gastrostomy was performed 130 years ago. Although it is difficult to ascertain the exact number of gastrostomy or jejunostomy tubes placed annually in the United States, it is estimated approximately 230,000 gastrostomy procedures were performed in U.S. hospitals in 2001. Of these, 11,000 were performed in children. Despite the many years gastrostomy tubes have been in use, they are not free from complications. The purpose of this article is to review the authors' experience with pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Antimicrobials Topical antibiotics (Chand, 2004;Fr€ ohlich et al, 2010;Goldberg et al, 2005;Heuschkel et al, 2015;Lee & Spratling, 2014;Lewis et al, 2008;Puntis, 2009;Soscia & Friedman, 2011) -Mupirocin (Goldberg et al, 2005;Soscia & Friedman, 2011) -Bacitracin/Polymyxin B (Soscia & Friedman, 2011) -Fucidin (Soscia & Friedman, 2011) -Cadexomer Iodine and foam dressing (Puntis, 2009) Oral antibiotics (Baker et al, 2013;Brook, 2002;Franken et al, 2015;Goldberg et al, 2005Goldberg et al, , 2010Heuschkel et al, 2015;Lee & Spratling, 2014;Puntis, 2009;Soscia & Friedman, 2011) -Cephalexin (Goldberg et al, 2005 (Soscia & Friedman, 2011) to several days with concurrent use of an alternative feeding method such as a nasoduodenal catheter (Franken et al, 2015). In terms of tube replacement, some authors suggested temporarily inserting a smaller tube to prevent full closure (Goldberg et al, 2005). Additionally, several expert opinion papers strongly cautioned against inserting wider tubes to avoid the risk of further enlarging the stoma (Lukish, 2010;Puntis, 2009).…”
Section: Category Subcategories Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Antimicrobials Topical antibiotics (Chand, 2004;Fr€ ohlich et al, 2010;Goldberg et al, 2005;Heuschkel et al, 2015;Lee & Spratling, 2014;Lewis et al, 2008;Puntis, 2009;Soscia & Friedman, 2011) -Mupirocin (Goldberg et al, 2005;Soscia & Friedman, 2011) -Bacitracin/Polymyxin B (Soscia & Friedman, 2011) -Fucidin (Soscia & Friedman, 2011) -Cadexomer Iodine and foam dressing (Puntis, 2009) Oral antibiotics (Baker et al, 2013;Brook, 2002;Franken et al, 2015;Goldberg et al, 2005Goldberg et al, , 2010Heuschkel et al, 2015;Lee & Spratling, 2014;Puntis, 2009;Soscia & Friedman, 2011) -Cephalexin (Goldberg et al, 2005 (Soscia & Friedman, 2011) to several days with concurrent use of an alternative feeding method such as a nasoduodenal catheter (Franken et al, 2015). In terms of tube replacement, some authors suggested temporarily inserting a smaller tube to prevent full closure (Goldberg et al, 2005). Additionally, several expert opinion papers strongly cautioned against inserting wider tubes to avoid the risk of further enlarging the stoma (Lukish, 2010;Puntis, 2009).…”
Section: Category Subcategories Examplesmentioning
confidence: 99%
“…Topical steroids (Crawley-Coha, 2004;Fr€ ohlich et al, 2010;Goldberg et al, 2005Goldberg et al, , 2010Hannah & John, 2013;Heuschkel et al, 2015;Lukish, 2010;Puntis, 2009;Rogers, 2004) -Triamcinolone cream -0.1% (Crawley-Coha, 2004;Goldberg et al, 2005Goldberg et al, , 2010Rogers, 2004) -0.5% (Crawley-Coha, 2004;Rogers, 2004) -Hydrocortisone 1% (Lukish, 2010;Puntis, 2009) -Fludroxycortide (Puntis, 2009) -Mometasone (Puntis, 2009) Oedema management Salt (Friedman, 2004;Soscia & Friedman, 2011;Tanaka et al, 2013) -Sprinkling salt (Tanaka et al, 2013) -Saline compresses (Friedman, 2004;Soscia & Friedman, 2011) Dressings (Chand, 2004;Crawley-Coha, 2004) -Polyurethane foam (Chand, 2004;Crawley-Coha, 2004) Stomahesive powder (Goldberg et al, 2005(Goldberg et al, , 2010) -…”
Section: Antiinflammatoriesmentioning
confidence: 99%
See 1 more Smart Citation